Modelling interactions between vector-borne diseases and environment using GIS - Khormi, Hassan M., 1984-; Kumar, Lalit, 1960- (CRC Press, 2015)
"This timely and groundbreaking book demonstrates how to develop models of vector borne disease risks based on different environmental and socioeconomic variables and to assess the association between these variables and their vectors in a Geographic Information System (GIS) environment. It addresses new spatial approaches and techniques based on location and environment and introduces methods to identify, determine, and analyze the trend, movement, and distribution of diseases and the vectors that transmit disease"-- Provided by publisher.
Keywords: Communicable diseases -- Mathematical models.; Communicable diseases -- Epidemiology -- Mathematical models.; Communicable diseases -- Prevention.; Communicable diseases -- Control.; Animals as carriers of disease.; Geographic information systems.; Geographic information systems -- Mathematical models.; Spatial analysis (Statistics); elektronické knihy; electronic books